Peran Gender dalam Pengaruh Gaya Hidup dan Literasi Finansial terhadap Perilaku Konsumtif Mahasiswa - Kurniawan, Muchammad Akbar; Safitri, Wiwit Nahdiyah; Sari, Angeli Carissa; Mustikawan, Alfin (IAIN Madura, 2025)
This research discusses consumptive behaviour among teenagers, especially university students, which is influenced by lifestyle, financial literacy, and gender factors. Consumptive behaviour arises as a result of social pressure, a culture of consumerism, and the urge to follow trends. Financial literacy is an important key in reducing this behaviour, by providing an understanding of effective financial management. The study used a quantitative approach with Structural Equation Modelling (SEM) and Multi-Group Analysis (MGA) methods, involving 86 social studies education students in Malang who were selected through random sampling techniques. The results of the analysis show that financial literacy has a significant influence in reducing consumptive behaviour, with variations in influence based on gender. This study highlights the importance of financial literacy and inclusive financial education to support better financial management among university students.